Determinants of Nurse Self-Efficacy and Infection Prevention Competency on Hospital Quality of Care - Nonalisa Nurindah; Ferdi Antonio (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
This study aims to analyze the factors that influence nurse-reported quality of care in medical personnel by involving 207 nurses as a sample. Six constructs were tested, namely care delivery, nurse professionalism, professional skill, professional development capability, organizational collaboration ability, and nurse personal trait. The method used was a quantitative cross-sectional method using Partial Least Squares–Structural Equation Modeling through SmartPLS4 software to see the structural relationship between variables and identify the factors that most influence the quality of care based on nurses’ perceptions. The results showed that most of the hypotheses were supported. Nursing services significantly influenced nurses’ infection prevention professional skills, professional development capabilities, organizational collaboration, and personal traits. Nurse professionalism had a great impact on professional skills, ability to develop professionally, and individual qualities, but did not affect the collaboration in the organization. The personal traits did not have a direct effect, whereas the quality of nursing services depended mainly on the professional development capabilities, skills of preventing infections, and collaboration of the organization. These results prove that the professional competence of nurses is one of the primary factors that define the quality of the services, and it is essential to reinforce competency-based training and lifelong learning.